Pengaruh Beban Kerja, Lingkungan Kerja, Komunikasi Terhadap Kinerja Karyawan KUD Sumber Barokah Kabupaten Musi Banyuasin - Umi Monirotul Badriyah; Yusro Hakimah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The researchers in this study aimed to examine how well employees of the Sumber Barokah Cooperative (KUD) in Musi Banyuasin Regency manage their workload, their perceptions of working conditions, and their communication with each other. This study used quantitative methods and a descriptive approach. All KUD Sumber Barokah personnel constituted the study population, and 49 participants were randomly selected using a saturated sampling technique. IBM SPSS 26 software was used to analyze the data using multiple linear regression analysis. The results showed that employee performance was positively influenced by communication, work environment, and workload. Employee performance was significantly influenced by the work environment and communication, but workload also had a significant negative influence. These results emphasize the importance of good communication, a positive work atmosphere, and effective work management in improving employee performance.